Meningkatkan Kompetensi Guru sebagai Peneliti Pendidikan melalui Pelatihan Penelitian Tindakan Kelas - Santosa, Heru; Supadi, Supadi; Soraya, Evitha (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Quality teachers are those who at least fulfil the academic qualifications of having a Bachelor degree in the field of Education and the required competencies. But in fact, the continuous professional development for school improvement through the practice of systematic reflection of teaching improvement in the form of conducting classroom action research is still dissatisfactory. Seeing this fact, such activity as workshops to improve classroom action research skills through community service are needed. The design of this activity follows the Community-Based Participatory Research Design (CBPR). This design consists of five steps Formulation of Research Problems, Collecting Data through Interviews, Compiling Interview Results, Regrouping, Clustered Discussion, Modification of Research Problems. In this community service, the target participants were 25 teachers of SMPN Pulo Gadung District. The training activities have many benefits for both parties, the research team and the teacher team. These benefits are the establishment of coordination, communication and cooperation in order to improve the quality of education, especially in improving teacher competence in conducting PTK.